2006
DOI: 10.1001/archpedi.160.11.1159
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Parent Perceptions on Youth Participation in Risk Behavior Research

Abstract: Parents and adolescents believed risk behavior research with adolescents was important. Most parents believed parental permission is needed for participation. Compared with parents, fewer adolescents believed parental consent was necessary. It is not clear what effect requirement of parental permission would have on participation or validity. Further research is needed to elucidate views on adolescent risk behavior research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Several studies have previously shown a tendency of African American and Hispanic/Latino populations to endorse spiritually based health-related behaviors [1,31]. Additional evidence supports the notion that parental consent perceptions of teens and their parents may vary among different ethnic groups [32]. A higher proportion of minority participants in Study 2 could also partially explain why CRAFFT scores are lower, since drug and alcohol use rates tend to be lower among black adolescents compared with white and Hispanic adolescents [33].…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have previously shown a tendency of African American and Hispanic/Latino populations to endorse spiritually based health-related behaviors [1,31]. Additional evidence supports the notion that parental consent perceptions of teens and their parents may vary among different ethnic groups [32]. A higher proportion of minority participants in Study 2 could also partially explain why CRAFFT scores are lower, since drug and alcohol use rates tend to be lower among black adolescents compared with white and Hispanic adolescents [33].…”
Section: Discussionsupporting
confidence: 54%
“…The underlying assumption is that parents have the ability to understand research and assess harms, over and above that of their adolescent children [20]. However, parents and their children do not always agree on the need for consent; parents' opinions are often informed by their own experience of adolescence (rather than the realities of their children's experience), and their willingness to consent changes with topic matter and scope of research [21,22]. Sexuality and sexual health are often difficult topics for parents to discuss with their children, and there remains ongoing confusion about the role of formal and informal sex education strategies [23].…”
Section: Mandating Parental Consent May Be Inconsistent With the Prinmentioning
confidence: 99%
“…Furthermore, there has been a concentration in the topical areas of parental and adolescent consent (Pasternak et al, 2006a; Vitiello et al, 2007). However, the introduction of biomarkers into research often requires more invasive and burdensome procedures.…”
Section: Introductionmentioning
confidence: 99%